Alpha-Ketoglutarate Curbs Differentiation and Induces Cell Death in Mesenchymal Stromal Precursors with Mitochondrial Dysfunction. (2nd May 2017) - Singh, Karmveer; Krug, Linda; Basu, Abhijit; Meyer, Patrick; Treiber, Nicolai; Vander Beken, Seppe; Wlaschek, Meinhard; Kochanek, Stefan; Bloch, Wilhelm; Geiger, Hartmut; Maity, Pallab; Scharffetter-Kochanek, Karin
Abstract : Increased concentrations of reactive oxygen species (ROS) originating from dysfunctional mitochondria contribute to diverse aging-related degenerative disorders. But so far little is known about the impact of distinct ROS on metabolism and fate of stromal precursor cells. Here, we demonstrate that an increase in superoxide anion radicals due to superoxide dismutase 2 (Sod2) deficiency in stromal precursor cells suppress osteogenic and adipogenic differentiation through fundamental changes in the global metabolite landscape. Our data identify impairment of the pyruvate and l -glutamine metabolism causing toxic accumulation of alpha-ketoglutarate in the Sod2 -deficient and intrinsically aged stromal precursor cells as a major cause for their reduced lineage differentiation. Alpha-ketoglutarate accumulation led to enhanced nucleocytoplasmic vacuolation and chromatin condensation-mediated cell death in Sod2 -deficient stromal precursor cells as a consequence of DNA damage, Hif-1α instability, and reduced histone H3 (Lys27) acetylation. These findings hold promise for prevention and treatment of mitochondrial disorders commonly associated with aged individuals.